1999
DOI: 10.1017/s002966519900052x
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated fatty acids

Abstract: There is good scientific evidence that dietary fatty acid composition is involved in the aetiology of many diseases. Increasing the supply of n−3 polyunsaturated fatty acids (PUFA) may reduce the risk of CHD. Several scientific organizations (for example, see Department of Health, 1991, 1994; British Nutrition Foundation, 1992; Scientific Committee for Food, 1993; Food and Agriculture Organization/World Health Organization, 1998) have made recommendations for n−3 PUFA; however, there is a high degree of variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1
9

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 26 publications
3
62
1
9
Order By: Relevance
“…Polyunsaturated fatty acids (PUFA) are designated as "essential" for good health as their metabolic precursors cannot be synthesised in the body and must be ingested by food intake [4]. PUFA have important effects on the structure and physical properties of localised membrane domains.…”
Section: Introductionmentioning
confidence: 99%
“…Polyunsaturated fatty acids (PUFA) are designated as "essential" for good health as their metabolic precursors cannot be synthesised in the body and must be ingested by food intake [4]. PUFA have important effects on the structure and physical properties of localised membrane domains.…”
Section: Introductionmentioning
confidence: 99%
“…Este pode ser um dos motivos pelos quais animais recebendo alimentação em pastagem apresentaram teores bem mais elevados de w-3 na carne, 1,03 e 2,9%, respectivamente (ENSER et al, 1996;RULE et al, 2002). Apesar de saber que o consumo de AGPI w-3 reduz o risco de doenças cardiovasculares, grande porcentagem da população (mais de 65%) não ingere peixe, que é uma boa fonte nutricional desse componente (ROCHE, 1999), por seu custo ou por não fazer parte do hábito alimentar da região.…”
Section: Resultsunclassified
“…Several o-3 fatty acid supplements are also available, but these provide varying amounts of marine-based EPA and DHA (Carroll & Roth, 2002;von Schacky, 2003). However, a-ALA, which serves as a precursor of EPA, is also a polyunsaturated o-3 fatty acid, and is found primarily in plant products such as soybeans, canola oil, flaxseed oil, and leafy vegetables (Roche, 1999). In a number of epidemiological studies, the consumption of food rich in ALA was found to be correlated with reduced morbidity and mortality from cardiovascular causes (de Lorgeril et al, 1999;Djoussé et al, 2001;von Schacky, 2003).…”
Section: Sources Of X-3 Fatty Acidsmentioning
confidence: 99%